LEGAL ANALYSIS OF THE USE OF CIRCUMSTANTIAL EVIDENCE THEORY: STUDY OF THE SUPREME COURT DECISION NUMBER 777/Pid.B/2016/ PN JAKARTA PUSAT - Wulandari, Cahya (Faculty of Law, Universitas Sebelas Maret, 2018)
As the provisions of Article 183 of the Criminal Procedure Code, the system or theory of proof embraced in Indonesia is a negative evidentiary system of law which, in the case of proof, is based on the evidences established in the law which may provide the judge's confidence. Based on the above matter, the existence of Decision Number 777 / Pid.b / 2016 / PN Jakarta Pusat is important to be studied in the judgment. The judge gives the verdict by using circumstantial evidence proof theory. The case was decided entirely using indirect evidence because there was no eye witness or other direct evidence that could prove the indictment. The discussion was conducted using qualitative approach with normative juridical method. Circumstantial evidence is new among practitioners, legal arguments from experts are needed to sharpen the analysis. The juridical review of the use of circumstantial evidence is divided into two categories that are recognized by the KUHAP and which are not recognized. Circumstantial evidence can be a solution for judges in verifying cases that are considered difficult. In a law-based State, the use of circumstantial evidence theory requires the regulation of valid evidence in accordance with the current development of cases.